1989
DOI: 10.1111/j.1472-8206.1989.tb00667.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Turpentine‐induced Inflammation on the Disposition Kinetics of Propranolol, Metoprolol, and Antipyrine in the Rat

Abstract: Plasma concentrations after oral administration of the high extraction drug propranolol are increased in patients and animals with inflammation. This could be due to increased serum propranolol binding, but also to decreased first-pass metabolism. We studied the pharmacokinetics of 3 drugs in control rats and in rats with turpentine-induced inflammation: propranolol, which is bound extensively to alpha 1-acid glycoprotein (alpha 1-AGP); metoprolol, another high extraction drug, but which is negligibly bound to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 13 publications
1
32
0
Order By: Relevance
“…The similar disposition of sotalol enantiomers in the healthy and in¯amed rats is due, perhaps, to negligible binding to plasma proteins and its complete (Anderson & Prystowsky, 1999). Hence, the two major in¯ammation-induced changes, i.e., increased serum a 1 -acid glycoproteins and decreased intrinsic hepatic clearance (Piafsky et al, 1978;Belpaire et al, 1989) do not play any signi®cant role in clearance of sotalol.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The similar disposition of sotalol enantiomers in the healthy and in¯amed rats is due, perhaps, to negligible binding to plasma proteins and its complete (Anderson & Prystowsky, 1999). Hence, the two major in¯ammation-induced changes, i.e., increased serum a 1 -acid glycoproteins and decreased intrinsic hepatic clearance (Piafsky et al, 1978;Belpaire et al, 1989) do not play any signi®cant role in clearance of sotalol.…”
Section: Discussionmentioning
confidence: 98%
“…In¯ammation causes increased concentrations of a 1 -acid glycoproteins (Piafsky et al, 1978) and reduced intrinsic clearance (Belpaire et al, 1989), both of which can result in increased circulating drug concentration. This renders dierentiation between the eects due to pharmacodynamics changes and those resulting from pharmacokinetic alterations dicult.…”
Section: Introductionmentioning
confidence: 99%
“…AA-induced inflammation also results in increased levels of acute-phase proteins, impaired drug-metabolizing enzymes, and, consequently, reduced clearance of a variety of drugs (Walker et al, 1986;Belpaire et al, 1989;Pollock et al, 1989;Piquette-Miller and Jamali, 1993;Emami et al, 1998). Although a widely used model, AA is associated with excessive pain and discomfort.…”
Section: Discussionmentioning
confidence: 99%
“…Although this model of inflammation has been used extensively to study pharmacokinetics of drugs (Walker et al, 1986;Belpaire et al, 1989;Pollock et al, 1989;Piquette-Miller and Jamali, 1993;Emami et al, 1998), it subjects animals to significant pain (Nagakura et al, 2003). AA causes increased expression of proinflammatory mediators, which is associated with suppression of hepatic metabolic processes, and, hence, reduces clearance of efficiently cleared drugs (Piquette-Miller and Jamali, 1993;Morgan, 1997;Kulmatycki and Jamali, 2001).…”
mentioning
confidence: 99%
“…Such inflammation-associated changes, which are collectively known as acute-phase responses, can result in profound increases in the plasma concentrations of various drugs, thereby causing toxic effects [1][2][3][4][5]. It was reported that cytochrome P-450 and chiral inversion activities are decreased in adjuvant-induced arthritis (AA) rats [6,7].…”
Section: Introductionmentioning
confidence: 99%